THE IMPLICATIONS OF USHUL LUGHAWIYAH PRINCIPLES IN UNDERSTANDING THE QUR’AN VERSES ON ECONOMY - Anggara, Windu; Amsari, Syahrul (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to analyze the implications of applying ushul lughawiyah principles to understanding the verses of the Qur’an about the economy. The research method used is a literature study with a qualitative approach. Data was collected through the analysis of various literature related to ushul lughawiyah principles and verses of the Qur’an about economics. The results of the research show that the application of ushul lughawiyah principles in understanding the verses of the Qur’an about the economy has important implications for understanding the meaning and messages contained in these verses. The ushul lughawiyah rule helps in identifying the meanings contained in the verses of the Qur’an about the economy and explains how these verses can be applied in a modern economic context. Some of the rules of ushul lughawiyah that are relevant in this context include the rules of takrir al-ma’ani, the rules of al-taqsir, the rules of al-istishab, the rules of al-istihsan, and the rules of al-mafhum. Through the application of these principles, important meanings can be identified in the verses of the Qur’an about the economy, such as the importance of investing, avoiding usury, maintaining equality in trade, and doing good in business. In conclusion, the application of ushul lughawiyah rules has important implications for understanding the verses of the Qur’an about the economy. These principles can help identify the meanings contained in these verses and explain how these verses can be applied in a modern economic context. The rules of al-istihsan, and the rules of al-mafhum. Through the application of these principles, important meanings can be identified in the verses of the Qur’an about the economy, such as the importance of investing, avoiding usury, maintaining equality in trade, and doing good in business. In conclusion, the application of ushul lughawiyah rules has important implications in understanding the verses of the Qur’an about the economy. These principles can help identify the meanings contained in these verses and explain how these verses can be applied in a modern economic context. The rules of al-istihsan, and the rules of al-mafhum. Through the application of these principles, important meanings can be identified in the verses of the Qur’an about the economy, such as the importance of investing, avoiding usury, maintaining equality in trade, and doing good in business. In conclusion, the application of ushul lughawiyah rules has important implications in understanding the verses of the Qur’an about the economy. These principles can help identify the meanings contained in these verses and explain how these verses can be applied in a modern economic context. Maintaining equality in trade and doing good in business. In conclusion, the application of ushul lughawiyah rules has important implications for understanding the verses of the Qur’an about the economy. These principles can help identify the meanings contained in these verses and explain how these verses can be applied in a modern economic context. Maintaining equality in trade and doing good in business. In conclusion, the application of ushul lughawiyah rules has important implications for understanding the verses of the Qur’an about the economy. These principles can help identify the meanings contained in these verses and explain how these verses can be applied in a modern economic context.